Comparison of Esophagectomy outcomes between a National Center, a National Audit Collaborative, and an International database using the Esophageal Complications Consensus Group (ECCG) standardized definitions. Issue 1 (27th June 2020) - Reynolds, John V; Donlon, Noel; Elliott, Jessie A; Donohoe, Claire; Ravi, Narayanasamy; Kuppusamy, Madhan Kumar; Low, Donald E
Summary: The ECCG developed a standardized platform for reporting operative complications, with consensus definitions. The Dutch Upper Gastrointestinal Cancer Audit (DUCA) published a national comparison against these benchmarks. This study compares ECCG data from the Irish National Center (INC) with both published benchmark studies. All patients undergoing multimodal therapy or surgery with curative intent from 2014 to 2018 inclusive were studied, with data recorded prospectively and entered onto a secure online database (Esodata.org). 219 patients (mean age 67; 77% male) underwent open resection, 66.6% via transthoracic en bloc resection. 30-day and 90-day mortality were 0.0 and 0.9%, nrespectively. Anastomotic leak rate was 5.4%, pneumonia 18.2%, respiratory failure 10%, ARDS 2.7%, atrial dysrhythmia 22.8%, recurrent nerve injury 3%, and delirium in 5% of patients. Compared with both ECCG and DUCA, where MIE constituted 47 and 86% of surgical approaches, respectively, overall complications were similar, as were severity of complications; however, anastomotic leak rate was several-fold less, and mortality was significantly lower (P < 0.001). In this consecutive series and comparative audit with benchmark averages from the ECCG and DUCA publications, a low mortality and anastomotic leak rate were the key differential findings. Although not risk stratified, the severity of complications from this 'open' series is consistent with series containing large numbers of total or hybrid MIE, highlighting a need to adhere to these strictly defined definitions in further prospective research and randomized studies.